In vitro and in vivo chemosensitizing activity of LFM-A13, a dual-function inhibitor of Bruton's tyrosine kinase and polo-like kinases, against human leukemic B-cell precursors - Uckun, Fatih; Dibirdik, Ilker; Sarkissian, Aniee; Qazi, Sanjive (Arzneimittelforschung, 2011)
The present study documents the chemosensitizing anti-leukemic activity of the leflunomide metabolite (LFM) analog, LFM-A13, a dual-function inhibitor of Bruton’s tyrosine kinase (BTK) and Pololike kinases (PLK), against human leukemic B-cell precursors. The results in 135 xenografted NOD/SCID mice regarding the anti-leukemic activity of GMP-grade LFM-A13, obtained with only 4-days of LFM-A13 therapy at nontoxic dose levels corresponding to 1 – 20 % of its NOAEL (no observable advserse effect level), alone or in combination with the standard chemotherapy drug vincristine, demonstrate the potential of LFM-A13 as a new anti-leukemic drug candidate. A11 82 LFM-A13-treated mice, including those receiving a combination of vincristine + LFM-A13 at the highest dose level of LFM-A13, tolerated their treatments well without weight loss, diarrhea, lethargy/paralysis, other signs of morbidity, or mortality.The present study provides preclinical proof-of-principle for the development of LFM-A13 as a new chemosensitizing and apoptosis-promoting anti-leukemic agent and lends support to the hypothesis that the chemoresistance of relapsed B-cell precursor acute lymphoblastic leukemia (BCP-ALL) can be overcome by using LFM-A13 in combination with chemotherapy. Also presented are the results of a comprehensive meta-analysis of the overexpression of genes for LFM-A13 targeted kinases and their downstream effector molecules in B-lineage lymphoid malignancies utilizing the Oncomine database.
Keywords: Anti-leukemic drug; Bruton's tyrosine kinase; inhibitor; LFM-A13; Polo-like kinases inhibitor; Vincristine; Xenografted NOD/SCID mice